The Comparative Study of Child and Women’s Rights Protection After Marital Dissolution in Indonesia and Philippines - Zuhdi, Syaifuddin; Alaba, Ma Daphnee; Kurnianingsih, Marisa; Prakoso, Andria Luhur; Fairuzzaman, Fahmi (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Abstract: Marriage dissolution through divorce or annulment often impacts the rights of children and women, necessitating strong legal protections. This study aims to compare the protection mechanisms for children's and women's rights after marital dissolution in Indonesia and the Philippines. Employing a normative-legal research method with a comparative approach, the study analyzes primary legal sources including Indonesia’s Marriage Law, Compilation of Islamic Law, Child Protection Law, and the Philippine Family Code and Constitution. The findings show that Indonesia provides two legal paths, divorce and annulment, offering a clearer framework for protecting post-marital rights, although enforcement remains inconsistent. Conversely, the Philippines, which only recognizes annulment for non-Muslims, faces challenges due to the absence of divorce, limiting access to legal remedies for women and children. Despite different legal systems, both countries prioritize the best interests of the child and uphold fundamental human rights principles. However, systemic obstacles, socio-cultural stigma, and gaps in implementation persist. The study concludes that enhancing the effectiveness of legal protections requires not only comprehensive legislation but also structural reforms to improve access to justice and empower vulnerable groups affected by marital dissolution. Abstrak Pembubaran perkawinan melalui perceraian atau pembatalan sering berdampak terhadap hak-hak anak dan perempuan, sehingga memerlukan perlindungan hukum yang kuat. Penelitian ini bertujuan membandingkan mekanisme perlindungan hak anak dan perempuan pasca pembubaran perkawinan di Indonesia dan Filipina. Dengan menggunakan metode penelitian hukum normatif dan pendekatan komparatif, studi ini menganalisis sumber hukum primer seperti Undang-Undang Perkawinan, Kompilasi Hukum Islam, Undang-Undang Perlindungan Anak di Indonesia, serta Family Code dan Konstitusi Filipina. Hasil penelitian menunjukkan bahwa Indonesia menyediakan dua jalur hukum, yaitu perceraian dan pembatalan, yang memberikan kerangka perlindungan lebih jelas, meskipun implementasinya masih menghadapi tantangan. Sebaliknya, Filipina yang hanya mengakui pembatalan bagi non-Muslim mengalami keterbatasan perlindungan akibat tiadanya mekanisme perceraian. Meskipun sistem hukum berbeda, kedua negara tetap mengutamakan kepentingan terbaik anak dan prinsip-prinsip hak asasi manusia. Namun demikian, hambatan sistemik, stigma sosial budaya, dan kesenjangan implementasi masih menjadi tantangan besar. Penelitian ini menyimpulkan bahwa untuk memperkuat perlindungan hukum, diperlukan tidak hanya legislasi yang komprehensif, tetapi juga reformasi struktural untuk meningkatkan akses keadilan dan memberdayakan kelompok rentan yang terdampak pembubaran perkawinan.